2006
DOI: 10.1080/17453670610045939
|View full text |Cite
|
Sign up to set email alerts
|

Detection of bony defects around cementless acetabular components in total hip arthroplasty: A DEXA study on 10 human cadavers

Abstract: Background We studied the ability of DEXA to detect bony defects around cementless acetabular components in total hip arthroplasty. The aim of our study was to provide a tool for detection and quantification of osteolytic lesions for the planning of revision cases.Methods We measured BMC in 10 human pelvis specimens retrieved from post mortem. We created standardized defects behind inserted acetabular components and compared the ash weights of the removed bone to the corresponding BMC measurements.Results We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…We went further in testing the reproducibility and quantifying of the model and concluded that it would be useful in detecting periacetabular osteolysis [9,10].…”
Section: Dexa Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…We went further in testing the reproducibility and quantifying of the model and concluded that it would be useful in detecting periacetabular osteolysis [9,10].…”
Section: Dexa Scanningmentioning
confidence: 99%
“…Measurements were performed with a dual energy X-ray absorptiometer (Norland XR-36 Bone Densitometer) as previously described [9,10]. We performed calibration daily, with two different phantoms, according to the instructions from the manufacturer.…”
Section: Dexa Scanningmentioning
confidence: 99%
“…Since osteolysis is implicated in the early phases of prosthetic loosening and failure, it is essential to accurately quantify periprosthetic osteolysis. Conventional radiology is not sensitive and accurate enough to detect small amounts of osteolysis, but dual energy x-ray absorptiometry (DEXA) is able to detect even small defects in the periprosthetic bone in the acetabulum [ 5 ]. In spite of the advantages of low wear and fewer dislocations, metal-on-metal hip prostheses increase systemic cobalt and chromium ion concentrations [ 6 ].…”
Section: Introductionmentioning
confidence: 99%